Strategi Pemasaran Digital Melalui Media Sosial dalam Meningkatkan Loyalitas Konsumen UMKM (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
The development of information technology has transformed the way micro,small,and medium enterprises (MSMES) market their products and interact with consumers.social media now plays a crucial role as a primary tool in digital marketing strategies due to its ability to reach consumers widely, quickly, and interactively. This study aims to analyze how digital marketing strategies through social media can enhance consumer loyalityamong MSMES. This research employs a qualitative descriptive approach, collecting data through in-depth interviews, observation of social media activities, and documentation of several MSMEs in medan. The findings reveal that consistent implementation of digital marketing strategies through social media significantly improves consumer loyalty. The main factors influencing this improvement include engaging content quality, active interaction between sellers and customers, and the effective use of social media features such as paid advertisements and collaborations with local influencers. The study concludes that digital marketing strategies through social media not only boost sales but also strengthen long-term relationships between MSMEs and their customers. Therefore, optimizing social media utilization becomes a strategic step for MSMEs to remain competitive in the digital era.